Use of maximum entropy in estimating production risks in crop farms - Cristian Kevorchian; Camelia Gavrilescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The entropic value of the production risk is closely linked to the farmer's aversion to this type of risk. Since risk aversion is difficult to quantify, it is preferable to use the MaxEnt model as a quantitative benchmark in assessing and covering the production risk through adequate financial resources. The classification of the Selyaninov index value as measure of the production risk based on the MaxEnt model utilization makes it possible to evaluate the production risk and the transfer decision to an adequate market implicitly. The authors' previous research investigated the risk coverage through derivative financial instruments that diminish the farmer's exposure to the production risk; the present paper adds to previous research by investigating an equally important issue: sizing the risk that is the object of coverage. Through the utilization of the stochastic methods in estimating the risk measure, a less rigid method is obtained that can be adapted and applied to the risk management processes in agriculture.
Keywords: 330; production risk; crop farms; Markov models; MaxEnt